Strategi Pengelolaan Karyawan dalam Meningkatkan Kinerja: Studi Kualitatif pada Staf Tenaga Kependidikan Bidang Administrasi, Umum, dan Keuangan Universitas Ngudi Waluyo - Adi Purwanto; Fitriyanto; Setya Indah Isnawati (Universitas Ngudi Waluyo, 2026)
Education personnel play a strategic role in supporting effective governance and service quality in higher education institutions. However, studies examining employee management strategies using the Ability, Motivation, Opportunity (AMO) framework remain limited, as previous research has predominantly focused on business and industrial sectors. This study aims to analyze employee management strategies for improving the performance of administrative, general affairs, and financial education personnel at Universitas Ngudi Waluyo based on the Ability–Motivation–Opportunity (AMO) framework. A qualitative approach with a case study design was employed. Thirteen informants, consisting of unit leaders and education personnel, were selected using purposive sampling based on their direct involvement in administrative, general affairs, and financial services. Data were collected through semi-structured interviews, non-participant observation, and document analysis. The data were analyzed using thematic analysis through the stages of coding, theme development, theme review, and conclusion drawing. The trustworthiness of the findings was ensured through source and method triangulation as well as member checking. The findings reveal that the ability dimension was strengthened through competency-based job placement, training, mentoring, and the enhancement of digital competencies. The motivation dimension was fostered through clear job responsibilities, performance evaluation, constructive feedback, recognition, leadership support, and a conducive work environment. Meanwhile, the opportunity dimension was realized through staff involvement in coordination, problem-solving, decision-making, cross-functional collaboration, and the effective utilization of organizational facilities and information systems. These three dimensions complement one another in enhancing service quality, work accuracy, responsiveness, accountability, and the overall effectiveness of administrative services in higher education. This study extends the application of the AMO framework to the context of education personnel in higher education institutions and provides practical recommendations for university leaders in designing integrated human resource management strategies to improve organizational performance. Abstrak Tenaga kependidikan memiliki peran strategis dalam mendukung efektivitas tata kelola dan kualitas pelayanan perguruan tinggi. Meskipun demikian, kajian mengenai strategi pengelolaan tenaga kependidikan dengan menggunakan kerangka Ability, Motivation, Opportunity (AMO) masih relatif terbatas, karena sebagian besar penelitian sebelumnya berfokus pada sektor bisnis dan industri. Penelitian ini bertujuan untuk menganalisis strategi pengelolaan karyawan dalam meningkatkan kinerja staf tenaga kependidikan bidang administrasi, umum, dan keuangan Universitas Ngudi Waluyo berdasarkan kerangka Ability–Motivation–Opportunity (AMO). Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus. Sebanyak 13 informan yang terdiri atas pimpinan unit dan staf tenaga kependidikan dipilih menggunakan teknik purposive sampling berdasarkan keterlibatan langsung dalam proses pelayanan administrasi, umum, dan keuangan. Data dikumpulkan melalui wawancara semi-terstruktur, observasi nonpartisipatif, dan studi dokumentasi. Analisis data dilakukan menggunakan analisis tematik melalui tahapan pengodean, pengembangan tema, peninjauan tema, dan penarikan kesimpulan, sedangkan keabsahan data dijaga melalui triangulasi sumber dan teknik serta member checking. Hasil penelitian menunjukkan bahwa dimensi ability diwujudkan melalui penempatan pegawai sesuai kompetensi, pelatihan, pendampingan, serta penguatan kemampuan digital. Dimensi motivation dibangun melalui kejelasan pembagian tugas, evaluasi kinerja, umpan balik, penghargaan, dukungan pimpinan, dan lingkungan kerja yang kondusif. Sementara itu, dimensi opportunity diwujudkan melalui pelibatan staf dalam koordinasi, penyelesaian masalah, pengambilan keputusan, kerja sama lintas unit, serta pemanfaatan fasilitas dan sistem informasi organisasi. Ketiga dimensi tersebut saling melengkapi dalam meningkatkan kualitas pelayanan, ketepatan kerja, responsivitas, akuntabilitas, dan efektivitas penyelenggaraan layanan administrasi perguruan tinggi. Penelitian ini memperluas penerapan teori AMO pada konteks tenaga kependidikan di perguruan tinggi serta memberikan rekomendasi bagi pimpinan perguruan tinggi dalam merancang strategi pengelolaan sumber daya manusia yang terintegrasi untuk meningkatkan kinerja organisasi.